Needle Choice in Spinal Anaesthesia: Is the 25-Gauge Whitacre Superior to the Quincke in Reducing Post-Dural Puncture Headache - Aniyat Ullah Sheikh; Rufaida Binta Jalal; Atul Khajuria; Deepanshu Sharma (Emerging Trends in Personalized Medicines, 2025)
The process known as endotracheal intubation involves inserting a synthetic tube into the trachea and inflating the former's cuff to create an airtight seal. Of all the specialised masks in the LMA family, the PLMA is the most intricate. The cuff, the airway tube, the drain (gastric access) tube, and the inflation line with pilot balloon are its four primary components. This drain tube aids in identifying mask malposition and offers a bypass channel for regurgitated stomach contents. The PLMA features a laryngeal cuff made from softer silicone and a deeper bowl design compared to the LMA Classic. These enhancements help create a more secure and effective seal around the larynx.A randomised, prospective study of 40 patients receiving general anaesthesia for an elective appendectomy at a GMC hospital has been taken into account. Extubation is typically done when the patient is starting to wake up and is in a lighter phase of anesthesia. This causes a marked rise in arterial blood pressure and heart rate that lasts into the recuperation phase. Insertion of the laryngeal mask eliminates the necessity for laryngoscopy and, consequently, the hemodynamic reactions. In our study, patients with normal blood pressure who had the ProSeal Laryngeal Mask Airway (PLMA) removed showed a rise in heart rate compared to their initial readings.At 5 minutes (86.92 ± 10.348) following tracheal extubation, this rise was very significant (PO.05). Antihypertensive drugs were given to all patients six hours before surgery. In patients with myocardial insufficiency, hypertension, cerebrovascular disease, and glaucoma, for example, where pressor reaction after extubation is to be avoided or is undesirable, PLMA is thought to be most helpful. Throughout the study, the main SpO₂ levels remained consistent across all groups, with no statistically significant differences observed. This finding held true regardless of whether laryngoscopy, arterial blood pressure, PLMA, LMA, or endotracheal intubation was involved.
Keywords: Proseal laryngeal mask airway (PLMA); endotracheal intubation; extubation; general anaesthesia; hemodynamic response